ANALISIS HUBUNGAN JOB EMBEDDEDNESS DENGAN KONFLIK KERJA-KELUARGA, KEPUASAN KERJA , KEPUASAN KELUARGA DAN KEPUASAN HIDUP, STUDI KASUS DI KPP PRATAMA PARE DAN KP2KP NGANJUK - Agus Pujiono (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Job Embeddedness is introduced to understanding why people stay in work, it;s includes (1) individual link to other people, teams, and groups, (2) perception of their fit with job organization, and community, and (3) what they say they would have to sacrifice if their left the jobs. We developed a measure of job embeddedness construct with test coreelation with job satisfaction, family satisfaction, work satisfaction and life satisfaction, the result show taht job embeddedness predict the key outcomes of both intent to leave and voluntary turnover and explain significant incremental variance over and above job satisfaction, organizational commitment, job alternatives, and job search. This article proposes refinements of the constructs of career mobility and career embeddedness and reviews the array of factors that have been found to energize (discourage) employees to change jobs, organizations, and/or occupations. The article also reviews the literature on career success and identifies which types of mobility (and embeddedness) are most likely to lead to objective career success (e.g., promotions) and subjective career success (e.g., career satisfaction). In the final section, the article revisits the utility of viewing careers as “boundaryless” and suggests alternative frameworks for future research on these topics.